Biomarkers in subtypes of mild cognitive impairment and subjective cognitive decline. Issue 9 (28th July 2017) - Eliassen, Carl F.; Reinvang, Ivar; Selnes, Per; Grambaite, Ramune; Fladby, Tormod; Hessen, Erik
Abstract: Objectives: Preclinical Alzheimers disease (AD) patients may or may not show cognitive impairment on testing. AD biomarkers are central to the identification of those at low, intermediate, or high risk of later dementia due to AD. We investigated biomarker distribution in those identified as subjective cognitive decline (SCD), amnestic (aMCI), and nonamnestic (naMCI) mild cognitive impairment (MCI) subtypes. In addition, the clinical groups were compared with controls on downstream neuroimaging markers. Materials and Methods: Cerebrospinal fluid (CSF) amyloid‐β42 (A β42) and total tau (t‐tau), phosphorylated tau (p‐tau), fluorodeoxyglucose (FDG), positron‐emission tomography (PET), and MRI neuroimaging measures were collected from 116 memory clinic patients. They were characterized as SCD, aMCI, and naMCI according to comprehensive neuropsychological criteria. ANOVAs were used to assess differences when biomarkers were treated as continuous variables and chi square analyses were used to assess group differences in distribution of biomarkers. Results: We did not find any between group differences in Aβ42, nor in p‐tau, but we observed elevated t‐tau in aMCI and SCD relative to the naMCI group. Significantly lower cortical glucose metabolism (as measured by FDG PET) was found in aMCI relative to SCD and controls, and there was a trend for lower metabolism in naMCI. Significant thinner entorhinal cortex (ERC) was found in aMCI and SCD. As expected biomarkers were significantly more frequently pathological in aMCI than in naMCI and SCD, whereas the naMCI and SCD groups displayed similar pathological biomarker burden. Conclusions: aMCI cases show the most pathologic biomarker burden. Interestingly naMCI and SCD subjects show similar levels of pathological biomarkers albeit the former displayed neuropsychological deficits. That the latter group may represent a risk group is supported by our observation of both elevated CSF tau and thinner ERC relative to controls. Abstract : Neuropsychological classification of mild cognitive impairment subtypes and those with subjective cognitive decline show different biomarker profiles.